2017
DOI: 10.1002/slct.201701075
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Crystallinity and Fluorescent Properties of LaF3 :Nd3+ Nanoparticles Synthesized with Different Water-Based Techniques

Abstract: We use two water based synthetic approaches to LaF 3 :Nd 3 + nanoparticles (NPs), hydrothermal microwave treatment (HTMW) and co-precipitation (CO) technique, with different temperature of the reaction mixture to study the correlation between the degree of crystallinity of LaF 3 :Nd 3 + NPs and their fluorescence properties. We showed that the fluorescence spectra and quenching kinetics can be a powerful tool to reveal the crystal lattice defects, namely agglomerations of the dopant ions (Nd 3 + ) and the OH À… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Synthesis of Er‐Yb@Yb‐Tm LaF 3 NPs—Materials : The samples were all synthesized in the Institute of Physics of the Universidade Federal de Alagoas by the coprecipitation technique in aqueous solution . Lanthanum (III) chloride (LaCl 3 , >99.99%), erbium (III) chloride (ErCl 3 , ≥99.99%), ytterbium chloride (YbCl 3 , 99.99%), thulium chloride (TmCl 3 , 99.99%), and ammonium fluoride (NH 4 F, ≥99.99%) were purchased from Sigma‐Aldrich.…”
Section: Methodsmentioning
confidence: 99%
“…Synthesis of Er‐Yb@Yb‐Tm LaF 3 NPs—Materials : The samples were all synthesized in the Institute of Physics of the Universidade Federal de Alagoas by the coprecipitation technique in aqueous solution . Lanthanum (III) chloride (LaCl 3 , >99.99%), erbium (III) chloride (ErCl 3 , ≥99.99%), ytterbium chloride (YbCl 3 , 99.99%), thulium chloride (TmCl 3 , 99.99%), and ammonium fluoride (NH 4 F, ≥99.99%) were purchased from Sigma‐Aldrich.…”
Section: Methodsmentioning
confidence: 99%
“…In [54], it is shown that the shape of rare-earth-doped dielectric NPs can affect the luminescence lifetime. Moreover, it is shown in [55] that the use of water-based coprecipitation method leads to the presence of OH groups into the NP's core as well. Hence, in the case of the MW-treated samples, the lifetime increasing can be attributed by two processes.…”
Section: Optical Spectroscopy and Luminescencementioning
confidence: 99%
“…e shape of the lifetime curves is more complicated obviously due to a set of different physical processes taking place in the NPs. In [36], the complicated shape of lifetime curves of Nd 3+ : LaF 3 NPs synthesized via the coprecipitation method is explained by the presence of defects such as water molecules in the NPs core as well as on the NPs surface and by inhomogeneous distribution of doping ions. For these reasons, the effective luminescence lifetimes (τ eff ) were calculated using equation (3) [39] in order to compare the lifetimes of the samples: Advances in Materials Science and Engineering…”
Section: Optical Spectroscopymentioning
confidence: 99%
“…ese phenomena affect the crystal field around the doping ions which makes the shape of the lifetime curves more complicated in comparison with analogous bulk crystals [35,36]. For these reasons, the modern theoretical approaches for some rare earth ions in some matrices are developed [36][37][38]. However, universal theories are still in the design phase.…”
Section: Introductionmentioning
confidence: 99%